2012
DOI: 10.5114/wo.2012.30055
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer properties of polysaccharides isolated from fungi of the Basidiomycetes class

Abstract: Basidiomycete mushrooms represent a valuable source of biologically active compounds with anticancer properties. This feature is primarily attributed to polysaccharides and their derivatives. The anticancer potential of polysaccharides is linked to their origin, composition and chemical structure, solubility and method of isolation. Moreover, their activity can be significantly increased by chemical modifications. Anticancer effects of polysaccharides can be expressed indirectly (immunostimulation) or directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 59 publications
(88 reference statements)
1
53
0
Order By: Relevance
“…It has been widely investigated and reported that fungal compounds have medical potential. In addition to their nutritional values, they possess antitumor, antibacterial, antiviral, and immunomodulatory activities [7,[22][23][24]. Their antitumor activity is often associated with the immunomodulatory activity.…”
Section: Resultsmentioning
confidence: 99%
“…It has been widely investigated and reported that fungal compounds have medical potential. In addition to their nutritional values, they possess antitumor, antibacterial, antiviral, and immunomodulatory activities [7,[22][23][24]. Their antitumor activity is often associated with the immunomodulatory activity.…”
Section: Resultsmentioning
confidence: 99%
“…Dietary fibres can help reduce blood cholesterol and protect against hypertension (Ching et al, 2011). Some $-glucans isolated from the mushroom fruit bodies have also been shown to stimulate the non-specific immune system inhibiting cancer cell proliferation (Lemieszek and Rzeski, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Lentinan was shown to stimulate the proliferation of blood mononuclear cells such as lymphocytes, monocytes, and macrophages and increase resistance to malignant transformation, and was demonstrated as an effective adjuvant for T cells [129]. Lentinan was shown to stimulate the proliferation of blood mononuclear cells such as lymphocytes, monocytes, and macrophages and increase resistance to malignant transformation, and was demonstrated as an effective adjuvant for T cells [129].…”
Section: Lentinan and Its Synthetic Analoguementioning
confidence: 99%